Measuring the Level of Public Service Quality Using SERVQUAL Method in Gayungan Village, Surabaya City - Hendrawan Widianto; Rizqa Amelia Zunaidi (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2024)
Kelurahan (village office) is the working area of lurah (village head), serving as a regional apparatus for developing economic facilities and public services. In this context, Gayungan Village has many problems arising from public opinion related to population registration, the need for correspondence, and the management of social assistance. Therefore, this research aimed to measure the level of public service quality as an evaluation material focused on tangibility, reliability, responsibility, assurance, and empathy dimensions. A quantitative analysis was adopted using service quality (servqual) method. The results showed that there was a discrepancy between expectations and reality in all dimensions. Tangibility, reliability, responsibility, assurance, and empathy dimensions obtained a gap value of -0.91, -1.06, -1.16, -1.04, and -0.88, respectively. Meanwhile, the improvement of public service quality should be carried out to appropriately meet the wishes and needs of the public.